The Dopant (N- and P-Type)-, Band Gap-, Size- and Stress-Dependent Field Electron Emission of Silicon Nanowires - Escrig-Murua, J; Kumar, C (Royal Society of Chemistry, 2024)
This study investigates the electron field emission (EFE) of vertical silicon nanowires (Si NWs) fabricated on n-type Si (100) and p-type Si (100) substrates using catalyst-induced etching (CIE). The impact of dopant types (n- and p-types), optical energy gap, crystallite size and stress on EFE parameters has been explored in detail. The surface morphology of grown SiNWs has been characterized by field emission scanning electron microscopy (FESEM), showing vertical, well aligned SiNWs. Optical absorption and Raman spectroscopy confirmed the presence of the quantum confinement (QC) effect. The EFE performance of the grown nanowire arrays has been examined through recorded J-E measurements under the Fowler-Nordheim framework. The Si NWs grown on p-type Si showed a minimum turn-on field and also a higher field enhancement factor. The band-bending diagram also suggests a lower barrier height of p-type Si NWs compared to n-type Si NWs, which plays a key role in enhancing the EFE performance. These investigations suggest that dopant types (n- and p-types), band gap, crystallite size and stress influence the EFE parameters and Si NWs grown on p-type Si (100) substrates are much more favorable for the investigation of EFE properties. © 2024 The Royal Society of Chemistry.